Metabolomic profiles of myocardial ischemia under treatment with salvianolic acid B - Lu Yonghai; Zheng Yue; Liu Xinru; Liang Xu; Ngai Saiming; Li Tiejun; Zhang Weidong (BMC, 2012)
Abstract Background Radix Salvia miltiorrhiza (Danshen) has been used as a principal herb in treating cardiovascular diseases in Chinese medicine. Salvianolic acid B (SA-B), a water-soluble active component of Danshen, was found to have anti-myocardial ischemia (anti-MI) effect. This study aims to investigate mechanisms of SA-B on MI. Methods Five conventional Western medicines (isosorbide dinitrate, verapamil, propranolol, captopril and trimethazine) with different mechanisms for treating cardiovascular diseases were selected as positive references to compare with SA-B in changing of the metabolomic profiles in MI rats under treatment. Potential mechanisms of SA-B were further investigated in H9C2 cell line. Results The metabolomic profiles between SA-B- and propranolol-treated MI rats were similar, since there was a big overlap between the two groups in the PLS-DA score plot. Finally, it was demonstrated that SA-B exhibited a protective effect on MI mainly by decreasing the concentration of cyclic adenosine monophosphate (cAMP) and Ca2+ and inhibiting protein kinase A (PKA). Conclusion SA-B and propanolol exhibited similar metabolomic profiles, indicating that the two drugs might have a similar mechanism.